ANALISIS EFISIENSI BOILER CFB UNIT 3 MENGGUNAKAN METODE LANGSUNG DI PT PLN INDONESIA POWER OMU JERANJANG - I Wayan Joniarta; Rashid Ridho Al Buhori; Made Wijana (Energy, Materials and Product Design, 2024)
A Boilers play an important role as steam power plants. A boiler is a closed vessel that is used to produce pressurized steam, where the resulting pressurized steam is used outside the boiler itself. This research aims to find out how to analyze the efficiency of CFB boilers. The analytical method used is the direct method. The results obtained show that the efficiency value of CFB boiler unit 3 of PLTU Jeranjang with a load of 25.8 MW, namely 73.17%, is quite low, this is caused by a lack of steam flow as a result of a leak in the upper boiler of PLTU Jeranjang unit 3, causing steam to come out of boiler and reduces its efficiency.